Análise da ADI 5.948/DF: a limitação do porte de arma de fogo das guardas municipais - Alves, Francisco Marcelo (Universidade Federal Rural do Semi-Árido, 2019)
This article makes an analysis of ADI 5.948 / DF, on the population limit for granting firearms to the Municipal Guards. Initially, it was pointed out the central problem of the research, which is the technical criterion used to justify the fact that municipalities with a population of less than 50,000 inhabitants can not have their Municipal Guard armed. In view of the growing concern about the issue of public safety, the importance of studying the role of municipalities in the above-mentioned area stands out. In relation to scientific knowledge, there is little doctrinal manifestation on the subject, since among the jurists few examined in depth the theme. Still in the context of the research, it was necessary to show the newly created "Single System of Public Security" that provides for the expansion of the institutional functions of the Municipal Guard in public security policies, as well as data sharing, operations and collaboration between Federal, State and Municipal, in which the Municipal Guard must integrate to act in a shared, systematic and harmonious way with the other institutions. The issue is important, since more and more municipalities are seeking to implement and structure their Municipal Guard, and one of the justifications presented for this is precisely the growing concern with insecurity in municipalities with lower population numbers. For these smaller municipalities, the question of the population factor as aspect for granting the carrying of a weapon may represent an obstacle to the execution of local security policies. This fact was treated in a preliminary manner through ADI 5.948 / DF, which Minister Alexandre de Morais determined that the effectiveness of one of the requirements for the granting of the possession of a weapon, which is the limitation from the criterion of the number of inhabitants. It should be noted that the methodology used was the documentary analysis of jurisprudence and the theoretical revision from the legal system and from the doctrinators who discuss the subject.
Keywords: Guarda Municipal; Quantitativo Populacional; Porte de Arma; Municipal Guard; Population Quantitative; Granting of Firearm; CIENCIAS SOCIAIS APLICADAS::DIREITO